Effect of different fertilizers and sowing date on growth, yield, and yield components of Sesame (Sesame indicum L.) - Naz Farhad Abdul-qader; Kawa Abdulkareem Ali (Zanco Journal of Pure and Applied Sciences, 2021)
A factorial experiment was conducted on the summer season of 2019 at two locations Grdarasha experimental field (Latitude: 36° 4’ N and Longitude: 44° 2’ E- elevation 415 meters above Sea level), College of Agricultural Engineering sciences, Salahaddin University, Erbil Iraqi Kurdistan Region and Erbil Research Director field /Ainkawa (Latitude :’ 36° 14’ N, 43° 59 E, 420 meters above sea level) using factorial experiment arranged in randomized design to investigate the effect of Four different formula of fertilizers (NPK; NPK+ Magnesium and Micro elements (Zn, Fe); Magnesium and Micro elements (Zn, Fe); No fertilizer were added considered as control) on growth, yield and yield component of sesame crop (Sesame indicum L.) under three sowing dates (20th of May, 4th of June and 19th of June). Results showed a significant rapid increase of branches number per plant, number of capsules per plant, and number of seeds per capsule, 1000 seeds weight (g), biological yield, grain and straw yield (t ha-1) when treated with (NPK plus Magnesium and Micro elements) fertilizer compared to the control treatment at the first sowing date. An interaction between first sowing date and second Fertilization formula recorded highest value compared to the others treatments.